Low diversity of major histocompatibility complex (MHC) genes in endangered Malayan Tapir (Tapirus indicus) - Ismail, Nurul Adilah; Christina, Seok Yien Yong; Simon, Yung Wa Sin; Annavi, Geetha (Academia Sinica, Taiwan, 2023)
The Malayan tapir (Tapirus indicus) is listed as Endangered on the IUCN Red List due to multiple threats such as habitat loss and human disturbance that have led to its population decline. This decline increases the risk of inbreeding, which could result in the reduction of genome-wide genetic variation and negatively affect the gene responsible for immune response i.e., MHC gene. Class I and II MHC genes are responsible for encoding MHC molecules in the cells that recognise pathogenic peptides and present them to T-Cells on the cell surface for adaptive immune response. However, at present there is no study related to the MHC gene in Malayan tapir yet. This study characterises the MHC class I and II genes from seven individuals, investigates evidence of balancing selection and their relationships with homologous genes of other species. We identified at least one class I gene and four class II genes. Five sequences of alpha1 (α1) and four of alpha2 (α2) domains of class I alleles, two DRA, two DQA, three DRB and three DQB of class II alleles were isolated. α1 and α2 domains of class I and DRB domain of class II displayed evidence of selection with a higher rate of non-synonymous over synonymous substitutions. Within the DRB gene, 24 codons were found to be under selection where 10 are part of the codons forming the Antigen Binding Site. Genes sequences show species-specific monophyletic group formation except for class I and DRB genes with intersperse relationship in their phylogenetic trees which may indicate occurrence of trans-species polymorphism of allelic lineage. More studies using RNA samples are needed to identify the gene’s level of expression.